Children as victims of sexual crimes: how is the role of the police in Indonesia? Anak sebagai korban kejahatan seksual: bagaimana peran polisi di Indonesia? - Huda, Mohammad Arinal (Indonesian Journal of Police Studies, 2021)
The child is the greatest gift that god gives to the parents to be cared for and the protection of his rights by the people and the State. Children also have basic human rights, and have been stipulated both national and international legal instrument. Attention to the protection of human rights law in children is still minimal by the people and the State. Indonesia as a State of law must be able to protect the rights of children considering they are the future assets of the State that must be protected the protection of their rights. There have been many cases of sexual crimes in children due to lack of care from parents and no respect for the rights of children by the community. Lack of legal awareness by the community causes the victims of sexual crimes in children to continue. This paper is intended to analyze the role of police on providing the legal proetction for children as victim of sexual violence in Indonesia. The research emphaszied and found that in some cases, police cannot provide the enough protetcion to children due to the lack of facilities as well as laws and regulations. Eventhough there is Juvenile Criminal Justice System, in many cases, the victims not getting adequate protection, as well as restoring their rights. This research underlines that the national law only focuses on the imposition of punishment for perpetrators, not yet more oriented to how to restore victims' rights. In the case in this study, the criminal route does not provide much to the victim, so a breakthrough is needed by law enforcement officials in Indonesia.